Anti-dengue Vaccines: From Development to Clinical Trials - Pinheiro-Michelsen, Josilene Ramos; Souza, Rayane da Silva Oliveira; Santana, Itana Vivian Rocha; da Silva, Patrícia de Souza; Mendez, Erick Carvalho; Luiz, Wilson Barros; Amorim, Jaime Henrique (Frontiers in Immunology, 2020)
Dengue Virus (DENV) is an arbovirus (arthropod-borne virus). Four serotypes of DENV are responsible for the infectious disease called dengue that annually affects nearly 400 million people worldwide. Although there is only one vaccine formulation licensed for use in humans, there are other vaccine formulations under development that apply different strategies. In this review, we present information about anti-dengue vaccine formulations regarding development, pre-clinical tests and clinical trials. The improvement in vaccine development against dengue is much needed, but it should be considered that the correlate of protection is still uncertain. Neutralizing antibodies have been proposed as a correlate of protection, but this ignores the key role of T-cell mediated immunity in controlling DENV infection. It is important to confirm the accurate correlate of protection against DENV infection, and also to have other anti-dengue vaccine formulations licensed for use.